Cultural Influences and Transmedia Literacy: Informal Learning Among Emirati Adolescents - Darwish, Elsayed (2025)
This study explores the digital engagement and transmedia literacy of Emirati adolescents using a qualitative-dominant mixed-methods approach. By analyzing information gathered from surveys (n = 1,346), digital diaries, workshops, and interviews, the researchers discovered a significant disconnect between informal digital learning and formal education. Seventy-five percent of participants engaged in content creation, whether through active or hybrid means, while 25 % primarily consumed content passively. Only 15 % felt their digital skills were recognized in academic settings; 60 % reported no recognition, and 25 % remained uncertain. Cultural norms, parental oversight, and socioeconomic differences significantly influenced creative autonomy and access, thereby reinforcing educational inequities. Participants demonstrated basic skills in critical evaluation, but they lacked proficiency in transmedia storytelling and ethical decision-making. These findings emphasize the necessity for culturally responsive pedagogies and policies that incorporate informal learning practices while fostering equitable digital citizenship, effectively connecting emergent youth practices with formal educational frameworks.